2022
DOI: 10.1108/et-12-2021-0471
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing mobile-learning and CAP(E) lesson framework in improving the productive skills of learners in a hybrid environment

Abstract: PurposeResearch advocates for the use of good teaching practices and approaches while integrating technology in digitally enhanced learning. This is on the premise that previous studies on mobile learning have neglected this aspect of technology integration resulting in numerous challenges. Moreover, there is evidence in the literature showing a scarcity of studies on the use of mobile learning in teaching productive skills. On the other hand, linguists recommend the use of responsive lesson design frameworks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Similarly, from students' opinions, this study found that although their listening skills were not improved, lessons planned by integrating the CAPE framework in a mobile learning model were perceived as enjoyable. This result is in tandem with some authors' opinions that using mobile learning and good teaching practices may produce positive learning outcomes (Ironsi and Bensen Bostancı, 2023; Romero Rodríguez et al. , 2021).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similarly, from students' opinions, this study found that although their listening skills were not improved, lessons planned by integrating the CAPE framework in a mobile learning model were perceived as enjoyable. This result is in tandem with some authors' opinions that using mobile learning and good teaching practices may produce positive learning outcomes (Ironsi and Bensen Bostancı, 2023; Romero Rodríguez et al. , 2021).…”
Section: Discussionsupporting
confidence: 76%
“…However, given these varying positions concerning implementing technology in the classroom, some novel studies insist that incorporating good teaching practices, strategies and frameworks may assist in improving the learning outcomes in a technology-based instructional delivery (Romero-Rodr ıguez et al, 2020a). Moreover, some indications are that applying good teaching practices, strategies and frameworks could lead to positive learning outcomes (Ironsi and Bensen Bostancı, 2023), which could help improve technology acceptance among students/teachers, thereby enhancing perception concerning technology-based learning and mobile learning, specifically.…”
Section: Mobile Learning and Cap(e)mentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile learning alleviates the mental strain placed on pupils by lowering the quantity of content that must be taught to them in a particular period. Mobile learning is advantageous for its practicality, adaptability, and versatility in the context of contextual education [3,4].…”
Section: Introductionmentioning
confidence: 99%